Fossil woods from the Pato Raro Heights, Patagonia National Park, Aysén, Chile: A new paleobotanical assemblage at the Oligocene climate transition - Pujana, Roberto Roman; Bostelmann, J. Enrique; Ugalde, Raúl A.; Riquelme, Marcia P.; Torres, Teresa (Review of Palaeobotany and Palynology)
Eleven well-preserved fossil woods were collected from sediments of the San José Formation in the Pato Raro Heights, Chilean Patagonia. Based on their wood anatomy, the specimens were placed in six fossil species: Two conifers of the Podocarpaceae (Phyllocladoxylon antarcticum and a new species of Podocarpoxylon with abundant resin content), one species of the Nothofagaceae (Nothofagoxylon ruei) and one of the Cunoniaceae (Weinmannioxylon trichospermoides), both previously described from Patagonia, a new species of Myrtineoxylon, with the typical anatomy of the family Myrtaceae, and a new taxon with unknown affinity, which was placed in a new fossil genus and species. The assemblage studied provides insights into the Oligocene forests of Patagonia and helps to fill a gap in the knowledge of the Oligocene paleofloras of the region. Fil: Pujana, Roberto Roman. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Bostelmann, J. Enrique. Universidad Austral de Chile; Chile Fil: Ugalde, Raúl A. Universidad Mayor; Chile Fil: Riquelme, Marcia P. Universidad Andrés Bello; Chile Fil: Torres, Teresa. Universidad de Chile; Chile